DC-Link Voltage Balancing Modulation for Cascaded H-Bridge Converters - Youngjong Ko; Anatolii Tcai; Marco Liserre (IEEE Access, 2021)
Cascaded H-Bridge (CHB) converters have been widely employed in various applications, providing the advantages of modularity and multilevel voltage output. However, technically the CHB converters require isolated DC-link buses, which need to be regulated individually. In this context, a control scheme for the CHB converters features the voltage balancing algorithm. The voltage balancing control is typically performed by PI controller, where its control capability is limited by linear modulation region. In this work, the modulation based voltage balancing algorithm is proposed, which extends the balancing control capability and improves the dynamic performance. The proposed method is theoretically analyzed and validated through the simulation and experimental results.